Edukasi Perilaku Hidup Bersih dan Sehat serta Etika Batuk Bersin Di Desa Sumber Jeruk Kabupaten Bondowoso - Rohmadoni, Alfi Rizqi Oktafi; Aninda Nyoka Sari; Septiana Bintang Maharani; Denok Risky Ayu Paramita; Rosida (Fakultas Kedokteran Gigi, Universitas Jember, 2025)
Clean and Healthy Living Behaviors (PHBS) are preventive measures to prevent tropical diseases and improve public health. Good coughing and sneezing etiquette is very important to prevent the transmission of respiratory tract infections, especially in early childhood. The purpose of this community service activity is to increase the knowledge and skills of parents and kindergarten children in Sumber Jeruk Village, Bondowoso, regarding PHBS and proper coughing and sneezing etiquette. The methods used were health education, demonstrations, and hands-on practice with a participatory learning approach. The activity was attended by 25 mothers of students and 25 Al Amin kindergarten children. A direct question and answer session was conducted to measure the increase in participants' knowledge. Significant results were achieved in increasing knowledge on proper handwashing (92%) and coughing and sneezing etiquette (88%). The children were able to practice proper handwashing and coughing and sneezing etiquette well. This activity succeeded in raising public awareness about the importance of PHBS in daily life and provided practical skills to prevent the spread of disease.Keywords: PHBS, coughing sneezing etiquette, prevention of tropical disease, health education